Overview of the Lifestyle of Diabetics at the Padang Bulan Medan Health Center - Sri Martini; Helinida Saragih; Rotua Elvina Pakpahan; Derlina Agustina Hutagalung (International Journal Of Health Science, 2025)
Diabetes mellitus where there is a disruption in the process of blood sugar metabolism in the body, which results in increased blood sugar levels. One of the causes of high rates of diabetes mellitus is lifestyle, lifestyle is an individual's uniqueness that is used to achieve self-created goals. A lifestyle that can increase a person's risk of diabetes mellitus is an unhealthy lifestyle such as not maintaining a diet, never exercising, smoking and stress. This study aims to identify the lifestyle of diabetes mellitus sufferers at the Padang Bulan Medan Health Center. The research design used is descriptive. The sampling technique used is Purposive sampling with a total of 77 samples. Data collection using a lifestyle questionnaire. The study showed that most of the lifestyle categories were sufficient at 51.9%, the poor category was 42.9%, and the good category was 5.2%. It is expected that the head of the Padang Bulan Medan Health Center will involve health workers to provide counseling on a good lifestyle, always control and motivate diabetes mellitus sufferers to change their lifestyle for the better.